Unraveling molecular characteristic of fluoride neurotoxicity on U87 glial-like cells: insights from transcriptomic and proteomic approach - Puty, Bruna; Bittencourt, Leonardo Oliveira; Lima, Leidiane Alencar Oliveira; Plaça, Jéssica Rodrigues; Dionizio, Aline; Buzalaf, Marília Afonso Rabelo; Gomes, Bruno Duarte; de Oliveira, Edivaldo Herculano Correa; Lima, Rafael Rodrigues (Frontiers in Cellular Neuroscience, 2023)
The potential of fluoride (F) as a neurotoxicant in humans is still controversial in the literature. However, recent studies have raised the debate by showing different mechanism of F-induced neurotoxicity, as oxidative stress, energy metabolism and inflammation in the CNS. In the present study, we investigated the mechanistic action of two F concentration (0.095 µg/mL and 0.22 µg/mL) on gene and protein profile network using a human glial cell in vitro model over 10 days of exposure. A total of 823 genes and 2084 genes were modulated after exposure to 0.095 and 0.22 µg/mL F, respectively. Among them, 168 were found to be modulated by both concentrations. The number of changes in protein expression induced by F were 20 and 10, respectively. Gene Ontology annotations showed that the main terms were related to cellular metabolism, protein modification and cell death regulation pathways, such as the MAPKcascade, in a concentration independent manner. Proteomics confirmed the changes in energy metabolism and also provided evidence of F-induced changes in cytoskeleton components of glial cells. Our results not only reveal that F has the potential to modulate gene and protein profiles in human U87 glial-like cells overexposed to F, but also identify a possible role of this ion in cytoskeleton disorganization.